Acute Myeloid Leukemia Evolving from JAK 2-Positive Primary Myelofibrosis and Concomitant CD5-Negative Mantle Cell Lymphoma: A Case Report and Review of the Literature - Diana O. Treaba; Salwa Khedr; Shamlal Mangray; Cynthia Jackson; Jorge J. Castillo; Eric S. Winer (Case Reports in Hematology)
Primary myelofibrosis (formerly known as chronic idiopathic myelofibrosis), has the lowest incidence amongst the chronic myeloproliferative neoplasms and is characterized by a rather short median survival and a risk of progression to acute myeloid leukemia (AML) noted in a small subset of the cases, usually as a terminal event. As observed with other chronic myeloproliferative neoplasms, the bone marrow biopsy may harbor small lymphoid aggregates, often assumed reactive in nature. In our paper, we present a 70-year-old Caucasian male who was diagnosed with primary myelofibrosis, and after 8 years of followup and therapy developed an AML. The small lymphoid aggregates noted in his bone marrow were neoplastic in nature and represented bone marrow involvement by a CD5-negative mantle cell lymphoma (MCL) that presented without any associated lymphadenopathy. We reviewed the English medical literature to identify a single case report of simultaneous association of AML and a MCL in the bone marrow. The unusual association presented here suggests an increase in observer awareness to apparently benign lymphoid aggregates in chronic myeloproliferative neoplasms.